Ureteroscopy‐assisted puncture for ultrasonography‐guided renal access significantly improves overall treatment outcomes in endoscopic combined intrarenal surgery. (24th May 2021) - Taguchi, Kazumi; Yamashita, Shimpei; Hamamoto, Shuzo; Deguchi, Ryusuke; Kawase, Kengo; Okada, Tomoki; Kato, Taiki; Ando, Ryosuke; Okada, Atsushi; Kohjimoto, Yasuo; Hara, Isao; Yasui, Takahiro
Abstract : Objectives: To assess the impact and availability of ureteroscopy‐assisted puncture for percutaneous renal access during ultrasonography‐guided miniaturized (mini)‐endoscopic combined intrarenal surgery for large volume renal and/or proximal ureteral stones. Methods: We conducted a multi‐institutional retrospective cohort study for urolithiasis treatment. Data from a total of 313 patients who underwent mini‐endoscopic combined intrarenal surgery to treat renal and/or ureteral stones between January 2016 and April 2020 were collected. We compared the outcomes between ultrasonography‐guided mini‐endoscopic combined intrarenal surgery with and without ureteroscopy‐assisted puncture (ureteroscopy‐assisted puncture(+) group [ n  = 126] and ureteroscopy‐assisted puncture(−) group [ n  = 187] group, respectively). The primary outcome was requirement for additional surgical intervention. Secondary outcomes were stone‐free rate, complications and total procedure, fluoroscopy, hospital stay, and postoperative ureteral stent placement durations. Results: The ureteroscopy‐assisted puncture(+) group had a lower additional surgical intervention rate and a higher stone‐free rate immediately after and 3 months after surgery than the ureteroscopy‐assisted puncture(−) group (5.6% vs 19.7%, P  < 0.001; 82.5% vs 65.8%, P  = 0.001; 59.5% vs 44.6%, P  = 0.011). The median total procedure, fluoroscopy, and postoperative ureteral stent placement durations were 18 min, 3 min, and 5 days shorter, respectively, in the ureteroscopy‐assisted puncture(+) group. Multivariate analyses showed that ureteroscopy‐assisted puncture was associated with a decreased risk of additional surgical intervention (odds ratio 0.31, P  = 0.011) and postoperative infection (odds ratio 0.34, P  = 0.003) and decreased total procedure (estimate = −11 min; P  = 0.011), fluoroscopy (estimate = −3 min; P  = 0.034), and postoperative ureteral stent placement (estimate = −8 days; P  = 0.011) durations. Female patients and those with smaller stone volumes or without hydronephrosis were identified as ideal ureteroscopy‐assisted puncture candidates. Conclusions: Ureteroscopy‐assisted puncture during mini‐endoscopic combined intrarenal surgery could provide favorable surgical outcomes, especially in female patients without collecting system obstruction.